2016
DOI: 10.1007/s00122-016-2697-z
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study reveals novel elite allelic variations in seed oil content of Brassica napus

Abstract: A set of additive loci for seed oil content were identified using association mapping and one of the novel loci on the chromosome A5 was validated by linkage mapping. Increasing seed oil content is one of the most important goals in the breeding of oilseed crops including Brassica napus, yet the genetic basis for variations in this important trait remains unclear. By genome-wide association study of seed oil content using 521 B. napus accessions genotyped with the Brassica 60K SNP array, we identified 50 loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
153
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(166 citation statements)
references
References 56 publications
10
153
1
2
Order By: Relevance
“…In addition, the efficiencies of association analysis is determined by population size and maker density [63]. So the Brassica 60 K SNP array was performed for the genotype of 520 rapeseed accessions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the efficiencies of association analysis is determined by population size and maker density [63]. So the Brassica 60 K SNP array was performed for the genotype of 520 rapeseed accessions.…”
Section: Discussionmentioning
confidence: 99%
“…PCA was superior to the Q model in controlling false positives for the estimation of population structure5859. Therefore, a mixed linear model (MLM) was used to calculate the associations in all analyses by incorporating PCA and kinship data56.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the OC of rapeseed is mainly controlled by genotype and genotype × environment interactions (GE) [46]; in addition, it is governed by multiple genes mainly through additive effect, and thus can be altered through breeding and selection [710]. …”
Section: Introductionmentioning
confidence: 99%